Potential adverse outcomes of herbal preparation use in childhood. (17th October 2018) - Farrington, Rachael; Musgrave, Ian; Byard, Roger W.
Abstract: Aim: Complementary and alternative medicines are becoming increasingly popular worldwide with a variety of purported medicinal uses. These products are generally believed to be natural and therefore safe, with few adverse reactions. With this perception, parents are now taking their children to see practitioners prescribing these medicines as well as self‐prescribing. Despite this, there are issues regarding safety, efficacy and regulation, with increasing numbers of reports of adverse reactions to these products. Therefore, a mini‐review was conducted to ascertain the potential risks to children. Methods: A overview of literature was conducted to highlight the current use of complementary and alternative medicines in children and the possible risks associated with their use. Results: Infants and children may be more susceptible to harmful effects due to their immature physiology and metabolic pathways and different dosage requirements. Adverse reactions may also be caused by interactions with conventional medicines, contamination with heavy metals, and adulteration of filler products including other plant species or pharmaceutical agents. Conclusion: As complementary and alternative medicines become increasingly used alongside and with conventional drug therapy, there needs to be greater awareness and discussion among parents, complementary practitioners and medical practitioners to ensure the overall health and safety of children being exposed to these products. Abstract :